1989
DOI: 10.1039/f19898500363
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt–manganese oxide water-gas shift catalysts. A kinetic and mechanistic study

Abstract: An investigation of the mechanism of the water-gas shift reaction over a cobalt-manganese oxide catalyst (Co : Mn = 1 : 1) is described using both kinetic and model reagent studies. The reaction of methanol, ethanol and formic acid are discussed, and these reagents are used as model reactants to probe the reaction mechanism. Based on these kinetic and model reactant studies a mechanism for the water-gas shift reaction is proposed for this catalyst system. It is considered that the mechanism proceeds according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 2 publications
(2 reference statements)
0
9
0
2
Order By: Relevance
“…Water-gas shift reaction (WGSR, i.e., CO + H 2 O $ CO 2 + H 2 ) is an important process used to produce hydrogen or adjust the CO/H 2 molar ratio in synthesis gas [1][2][3]. An emerging application for the WGSR is in the field of fuel cell for removing CO, which is a strong poison of proton exchange membrane (PEM) anode catalysts [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Water-gas shift reaction (WGSR, i.e., CO + H 2 O $ CO 2 + H 2 ) is an important process used to produce hydrogen or adjust the CO/H 2 molar ratio in synthesis gas [1][2][3]. An emerging application for the WGSR is in the field of fuel cell for removing CO, which is a strong poison of proton exchange membrane (PEM) anode catalysts [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 + H 2 , DH = À41.1 kJ mol À1 ) has been widely investigated for CO removal and hydrogen production process. In general, a conventional WGS reactor comprises two stages with different temperature regions due to the thermodynamic limitation: high-temperature water-gas shift (HTS; 350-500 8C) using Fe 2 O 3 /Cr 2 O 3 and low temperature water-gas shift (LTS; 190-250 8C) using CuO/ZnO/Al 2 O 3 [3][4][5][6][7][8][9][10][11]. In this way, the 10-20% of CO contained in the gas was reduced after the reforming process to 3-5% at by HTS and then to below 1% carrying out by LTS [12].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting experimental study has reported that the reaction of the complex [Cp′ 2 Mo(OH)(OH 2 )] + (Cp′ = η 5 ‐C 5 H 4 CH 3 ) with CO in aqueous solution takes place in a relatively facile way, with 30 % conversion to the product complex [Cp′ 2 MoH(CO)] + in 1 h at 80 °C under CO (1 atm) 18. Given the experimental mechanistic investigations on the WGSR chemistry over ruthenium37 and cobalt–manganese32 catalysts, it has been proposed that the reaction mechanism for CO oxidation in the presence of aqueous molybdocenes consists of four steps (see Scheme ): (1) CO coordination to the metal center; (2) nucleophilic attack of hydroxide (or water) to the coordinated CO; (3) decarboxylation of the newly formed carboxylic acid group to give the monohydride [Cp′ 2 MoH] + ; and (4) addition of a second CO molecule to the metal center to finally afford [Cp′ 2 MoH(CO)] + 18. The nature of this complex has been confirmed by spectroscopic studies.…”
Section: Introductionmentioning
confidence: 99%